Financial Performance of Sugar Factories in Karnataka state - Patil, Ganeshgouda I; Mahajanashetti, S B; Patil, Somanagouda I (Indian Farming, 2017)
The financial ratio analysis of the selected public, private and cooperative sugar factories was got wider variation in the financial progress among these sectors due to the management of the factories system and scale of operation of the factories. However, with available strengths of the factories, not much appreciable financial progress was observed in any of the selected public, private and co-operative sugar factories. Further, for comparison of these factories among the three sectors, the (above average and below average) private and above average (co-operative) factories were aeliveving better financial progress. Whereas, other two below average co-operative factories and public sector factories, the situation is worst. Hence, these factories need to be strengthened either through the government financial assistance or these factories may be handed over to the private ownership management for improving their financial progress.